THE STATUS OF THE MINERAL RAW MATERIALS BASE OF PRECIOUS METALS OF RUSSIA AND THEIR ROLE IN THE MODERN ECONOMY - V. T. Borisovich; V. N. Ivanov; Z. M. Nazarova (Известия высших учебных заведений: Геология и разведка)
The current state of the mineral resource base of gold, silver, platinum and palladium for different geological and industrial types of deposits has been shown. For each of the given metals reserves, probable reserves and allocated fund of deposits in Russia have been given. For all bank precious metals volumes of the market offers have been given. Special attention has been paid to the use of the metals both in the world and in Russia. In the practice of market relations, the demand for precious metals can be divided into two types: fabrication (industrial) and hoarding (investment). Precious metals are used in jewelry, electronic, glass, nuclear, pharmaceutical, chemical, petrochemical and other industries. They find their application in medicine and biomedicine, automotive, microelectronics, aerospace instrument making, the manufacturing of lasers and nuclear tests. It has been noted that in our country a great disadvantage is the weak industrial use of precious metals.